Impact of Blockchain Enhanced Digital Marketing on Brand Awareness of Solar Panels - Adam Faturahman; Nada Shofa Lubis; Nizariah; Nuke Puji Lestri Santoso; Alfri Adiwijaya; Mihkel Madisson (IAIC Bangun Bangsa, 2025)
This research examines the impact of digital marketing and blockchain technology on enhancing brand awareness for solar panel products offered by PT REY, with a special focus on integrating local wisdom. As the renewable energy sector grows rapidly in Indonesia, solar panels have emerged as a promising solution. However, the challenge of low brand awareness remains significant for PT REY. Digital marketing is a crucial strategy to overcome this challenge and expand the company’s reach. In this study, Structural Equation Modeling (SEM) was used to analyze the relationship between digital marketing strategies, local wisdom, and brand awareness. The findings reveal that social media, websites, and visual content, structured strategically, effectively increase brand awareness and introduce solar panels to a wider audience. Additionally, integrating local wisdom into digital marketing campaigns enhances the emotional connection between the brand and its consumers, enriching the REY brand’s value. The results demonstrate that both digital marketing and local wisdom play significant roles in boosting brand awareness, with their combination having a stronger impact than using each element separately. This research offers valuable insights on how combining digital marketing, blockchain, and local wisdom can create a unique brand identity and provide competitive differentiation in the growing renewable energy industry in Indonesia. The findings contribute to promoting sustainable energy solutions while supporting businesses in building stronger brand identities